Determinants of Functional Response in Rheumatoid Arthritis Therapy. - Schoels, Monika. (2017)
Abstract: Background: Rheumatoid arthritis (RA) is an inflammatory condition that primarily affects the joints of the hands. If disease activity cannot be suppressed effectively, synovitis leads to loss of function. In recent years, biological therapies have made functional improvement possible for many patients, if effective treatment is initiated promptly. Because biologicals are expensive and carry risk for adverse effects, identifying those patients who are at high risk for limited functional response would select a subgroup that may benefit from rapid treatment escalation. Aim: To identify determinants of functional improvement during RA therapy. Methods: We analyzed observational data of RA patients who were starting a new therapy at two outpatient clinics. Using linear regression, we examined the impact of baseline radiographic damage assessed by Total Sharp Score (TSS), physical function evaluated with the Health Assessment Questionnaire (HAQ), clinical and laboratory inflammation markers, therapy, and patient characteristics on functional improvement during therapy. Results: We included 311 patients with a mean age of 61.5 years and average disease duration of 17.1 years in our analyses. Baseline radiographic damage (higher TSS) was significantly associated with HAQ worsening during a mean follow-up of 1.75 years. Over the entire TSS range (0-448 points), a 1 point elevation of TSS at baseline worsened HAQ by 0.002 units (95% CI 0.001-0.003). However, for baseline TSS scores between 30 and 70, HAQ progressed by 0.011 units per 1 unit rise in TSS (for men), versus 0.002 units for TSS>70. Patients with more baseline tender joints and those not treated with biological therapies had more HAQ progression, but patients with higher baseline HAQ, and more swollen joints had HAQ improvement. Conclusions: In a patient population with relatively low baseline radiographic damage despite 17 years of disease, a one point rise in TSS falling between 30 to 70 affects HAQ progression more so than TSS in other ranges. Our findings emphasize the importance of vigorous therapeutic efforts to prevent radiographic progression especially in this group.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Clinical & Translational Science.; Advisor: John Wong.; Keyword: Medicine.